Development of ceramic cutting tools for future application on dry machining - Silva, O. M M; Souza, J. V C; Nono, M. C A; Martins, G. V.; Ribeiro, M. V. [UNESP]; Machado, J. P B (Trans Tech Publications, 2010)
Advanced ceramic materials constitute a mature technology with a very broad base of current and potential applications and a growing list of material compositions. Within the advanced ceramics category, silicon nitride based ceramics are wear-resistant, corrosion-resistant and lightweight materials, and are superior to many materials with regard to stability in high-temperature environments. Because of this combination the silicon nitride ceramics have an especially high potential to resolve a wide number of machining problems in the industries. Presently the Si3N4 ceramic cutting tool inserts are developed using additives powders that are pressed and sintered in the form of a cutting tool insert at a temperature of 1850 °C using pressureless sintering. The microstructure of the material was observed and analyzed using XRD, SEM, and the mechanical response of this array microstructure was characterized for hardness Vickers and fracture toughness. The results show that Si3N4/20 wt.% (AlN and Y 2O3) gives the best balance between hardness Vickers and fracture toughness. The Si3N4/15 wt.% (AlN and Y 2O3) composition allows the production of a very fine-grained microstructure with low decreasing of the fracture toughness and increased hardness Vickers. These ceramic cutting tools present adequate characteristics for future application on dry machining. © (2010) Trans Tech Publications.
Keywords: Ceramics; Dry machining; New cutting tool; Si3N4; Advanced Ceramics; AlN; Array microstructure; Corrosion-resistant; Cutting tool inserts; Fine-grained microstructure; Future applications; High potential; High-temperature environment; Lightweight materials; Material compositions; Mechanical response; Potential applications; Pressureless sintering; SEM; SiN; Silicon nitride ceramics; Silicon nitride-based ceramics; Vickers; Wear-resistant; XRD; Ceramic materials; Ceramic tools; Cutting tools; Equipment; Fracture; Fracture toughness; Hardness; Machine tools; Machining; Metal working tools; Microstructure; Silicon; Silicon nitride; Sintering; Ceramic cutting tools